2020
DOI: 10.3389/fphar.2020.00718
|View full text |Cite
|
Sign up to set email alerts
|

Bilobalide Alleviated Dextran Sulfate Sodium-Induced Experimental Colitis by Inhibiting M1 Macrophage Polarization Through the NF-κB Signaling Pathway

Abstract: Bilobalide, a unique Ginkgo biloba constituent has attracted significant interest as a novel therapeutic option for neuronal protection. However, there is paucity of data on its effect on colitis. This work sought to evaluate the effect of bilobalide on macrophage polarization in vitro and dextran sulfate sodium (DSS) induced colitis in vivo. Through the 3-(4,5dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and annexin V/PI assay, it was shown that bilobalide has no significant toxicity on macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…However, the underlying mechanism of how lactic acid exerts its anti-inflammatory activities in colitis remains to be explored. Increasing evidence suggested that targeting macrophage polarization benefits UC treatment (33)(34)(35). The different polarization states of macrophages show diverse immunological responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the underlying mechanism of how lactic acid exerts its anti-inflammatory activities in colitis remains to be explored. Increasing evidence suggested that targeting macrophage polarization benefits UC treatment (33)(34)(35). The different polarization states of macrophages show diverse immunological responses.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggested that targeting macrophage polarization benefits UC treatment ( 33 35 ). The different polarization states of macrophages show diverse immunological responses.…”
Section: Discussionmentioning
confidence: 99%
“…Rats in the 5 mg/kg + Bilobalide and 10 mg/kg + Bilobalide groups received oral bilobalide daily for 6 weeks. The bilobalide dosage was based on previous studies ( Heng Zhang et al, 2020 ; Zhao et al, 2021 ). After 6 weeks of treatment, the rats in each group were euthanized by intraperitoneal injection of a lethal dose of ether, and their knee joints and blood samples were taken.…”
Section: Methodsmentioning
confidence: 99%
“…KEGG analysis revealed the activation of TNF/NF-κB signaling in LPS-treated macrophages from anti-Act1 mice. Shreds of literature had reported that the activated TNF/NF-κB signaling enhances M1-macrophage polarization ( Liu et al, 2017 ; Lu et al, 2020 ; Zhang H. et al, 2020 ). Inflammation triggers M1 macrophage polarization and M1 macrophages further release proinflammatory cytokines thereby amplifying inflammation in a vicious fashion in the periodontitis milieu.…”
Section: Discussionmentioning
confidence: 99%